"Dorsal–Ventral" Genes Are Part of an Ancient Axial Patterning System: Evidence from Trichoplax adhaerens (Placozoa). (6th February 2019) - DuBuc, Timothy Q; Ryan, Joseph F; Martindale, Mark Q
Abstract: Placozoa are a morphologically simplistic group of marine animals found globally in tropical and subtropical environments. They consist of two named species, Trichoplax adhaerens and more recently Hoilungia hongkongensis, both with roughly six morphologically distinct cell types. With a sequenced genome, a limited number of cell types, and a simple flattened morphology, Trichoplax is an ideal model organism from which to explore the biology of an animal with a cellular complexity analagous to that of the earliest animals. Using a new approach for identification of gene expression patterns, this research looks at the relationship of Chordin/TgfΒ signaling and the axial patterning system of Placozoa. Our results suggest that placozoans have an oral–aboral axis similar to cnidarians and that the parahoxozoan ancestor (common ancestor of Placozoa and Cnidaria) was likely radially symmetric.